Element interactivity as a factor influencing the effectiveness of worked example–problem solving and problem solving–worked example sequences. (29th August 2019) - Chen, Ouhao; Retnowati, Endah; Kalyuga, Slava
Abstract : Background: The worked example effect in cognitive load theory suggests that providing worked examples first followed by solving similar problems would facilitate students' learning. Using problem solving–worked example sequence is another way of implementing example‐based instruction. Although research has demonstrated the superiority of worked example–problem solving sequence on learning materials that presumably are high in element interactivity for novices, none of the previous studies have compared the two sequences with levels of element interactivity experimentally manipulated in a strictly controlled manner. Aim: The reported study aimed to investigate the effects of levels of element interactivity of the learning tasks and levels of learner prior knowledge on the effectiveness of two alternative example‐based sequences, worked example–problem solving versus problem solving–worked example. Sample: Fifty‐two Year five students, around 10 to 11 years old, from a primary school in Indonesia participated in Experiment 1, and 96 Year eight students, around 13 to 14 years old, from a secondary school in Indonesia participated in Experiment 2. Methods: 2 (sequences: worked example–problem solving vs. problem solving–worked example) × 2 (levels of element interactivity: low vs. high) experimental design, with the second factor repeatedly measured, was used in the two experiments conducted with learners at different levels of prior knowledge. Result: The results showed the advantage of using worked example–problem solving sequence for learning materials high in element interactivity, especially for novice learners, whereas there were no differences between the worked example–problem solving and problem solving–worked example sequences for learning materials low in element interactivity for more knowledgeable learners. Conclusion: This study not only replicated the results of previous studies, but also extended their findings by experimentally manipulating levels of element interactivity of learning materials.